Dialectics of Tradition and Modernization in the Constitutional Development of Russia - Kapitsyn, Vladimir (VNU Journal of Science: Legal Studies; Vol 38 No 1, 2022)
The Soviet project reflects the cultural, historical, economic, and ethnonational resources of non-Western modernization. The Marxist Party of the USSR controlled power by building an ideological and political-managerial vertical that connected Soviets, party, trade union, and other public associations, the press, enterprises, settlements, the army, schools, families, all generations of society, and art. “Perestroika” destroyed the ideological and political “core” of the soviet system (repeal of Article 6 of the Constitution). The separation of powers replaced the system of the Soviets. The Russian state has lost its political ideology, significantly weakened its security agencies and army, and lost a significant part of its economic potential. China and Vietnam took into account the costs of Soviet reforms, drew the appropriate conclusions and took a different political path, which Russian researchers have yet to study. Later, after 2000, new political reforms began in Russia, which made it possible to move on to the creation of the ideological and political "core" of the new state. Under Vladimir Putin, the institute of the presidency really formed such a political “core” that would help to gradually move along the path of consolidating the political system and society, solve national security issues, and revive the economy and the system of educating young people. Amendments to the Constitution Russia in 2020 summed up a certain result of the formation of a strong state.